Proposed Social Media Marketing Content Strategy Through Instagram to Increase Sales Performance Of Fashion Business (Case Study: DMC.id) - Putri, Rahma Hanum Kusuma; Windasari, Nila Armelia (Journal of Economics and Business UBS, 2023)
Dress Me Chic (DMC) is an online business, engaged in the fashion industry. DMC focuses on fast fashion selling Excess Clothing from Exports which exists to help women’s problems mainly in satisfying their basic needs, especially in fashion. DMC provides a wide variety of products to mix and match which are up-to-date and come with versatile designs. DMC comes with an “Affordably Stylish”, with a special price since DMC does business process innovation. The market target of DMC is a white-collar woman worker who has various activities. DMC's competition in the sector of fast fashion is surely expanding as the digital era develops.  DMC does not outperform in social media marketing in the digital era compared to rivals. This causes DMC's sales to show neither an increase nor a decrease in the past year. DMC's sales are not proportionate with the number of Social Media Instagram followers; hence, many followers are not consumers because they simply follow DMC’s Instagram and do not purchase. Due to this circumstance, DMC is attempting to concentrate on attracting customers using the social media Instagram in order to raise customer awareness. In order to make DMC competitive in the industry, this research aims to determine the best Social Media Marketing Content Strategy. This study analyses the issues that DMC account followers face on Instagram, specifically addressing the precise reasons why followers do not make purchases at DMC. The author identifies problems using Root Cause Analysis with the aim to identify the root cause of DMC’s social media that are not performing well. The author found that DMC has not created an attractive and right content strategy on social media that can facilitate the target market in ordering products.  The author applied quantitative & qualitative research on followers of the DMC’s Instagram, who rarely or had never bought DMC. As a result of the research, the author has proposed new content strategies in the form of Try-On Content, Mix & Match Content, CTA Content, Promo Content, and several contents based on customers’ opinions. This strategy is supported by a planned implementation structure adjusted to the time plan made and justification for the budget plan. This combination proposed the best plan for the target market, which assists in increasing the number of engagement conversions for improving sales performance.